Entropy per particle spikes in the transition metal dichalcogenides - Shubnyi, V.O.; Gusynin, V.P.; Sharapov, S.G.; Varlamov, A.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2018)
We derive a general expression for the entropy per particle as a function of chemical potential, temperature and gap magnitude for the single layer transition metal dichalcogenides. The electronic excitations in these mate-rials can be approximately regarded as two species of the massive or gapped fermions. Inside the smaller gap there is a region with zero density of states where the dependence of the entropy per particle on the chemical potential exhibits a huge dip-and-peak structure. The edge of the larger gap is accompanied by the discontinuity of the density of states that results in the peak in the dependence of the entropy per particle on the chemical potential. The specificity of the transition metal dichalcogenides makes possible the observation of these features at rather high temperatures order of 100 K. The influence of the uniaxial strain on the entropy per particle is discussed.